A Field Study on the Relationship between Employer Brand and Employee Satisfaction - Funda Yalım; Kagan Cen Mızrak (International Review of Management and Marketing, 2017)
Employees play a significant role in the success of establishments. The ensuring of employee satisfaction is an issue which should be examined carefully at this point. Today it is set forth with different studies that many elements are effective in ensuring employee satisfaction. This study was conducted towards the employees of an establishment with an important employer brand in our country in order to reveal the relationship of a powerful employer brand and the benefits that this brand promised to employees with employee satisfaction. Of the qualitative research methods, the questionnaire technique was used in the research. The results were analyzed with the SPSS (22.0) Statistical Program. The research findings reveal that the elements of employer brand are related to employee satisfaction and that the employer brand affects employee satisfaction. Besides, no significant difference could be found between the demographic characteristics of the participants and employee satisfaction. Keywords: Brand, employer brand, employee satisfaction JEL Classification: M